Play therapy and storytelling intervention on children's social skills with attention deficit-hyperactivity disorder - Afsaneh Karbasi Amel; Helia Rahnamaei; Zeinab Hashemi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Attention deficit-hyperactivity disorder (ADHD) is a common neuro-behavioral disorder that negatively affects educational, relational, and occupational aspects of one's life. Although many children diagnosed with this disorder can benefit from taking medication, particularly for core symptoms, play therapy and storytelling can be seen as engaging, stimulating, and more compatible with children's developmental needs. The social skills of these children are as vital as other symptoms and can be better addressed with cognitive-based art therapy interventions. Because little research has been focused on the combination of play therapy and storytelling and the social interactions of children with ADHD are highly important in academic settings, this study aimed to determine the effects of this combination on children's social skills with ADHD.MATERIALS AND METHODS: This survey was a quasi-experimental study with a pre-test-post-test design and a control group. Participants were 7-11-year-old girls and boys with ADHD based on DSM-V referred to child and adolescent psychiatrists' clinics. Selected children were randomly allocated into intervention and control groups. The intervention group received an individual combined intervention of play therapy and storytelling, whereas the control group did not receive any therapeutic intervention for social skills at that time and was on the waiting list. The research tool was the Social Skills Rating System (SSRS), and data were computer-analyzed using SPSS-20 and a couple of descriptive and analytic tests including ANCOVA.RESULTS: In this study, 30 children with ADHD were included. The combined intervention of play therapy and storytelling has had a significant effect on post-test results of ADHD patients in terms of social skills as well as all test subscales (P < 0/05). There was a significant improvement in the subscales of self-expression, self-control, responsibility, and cooperation (P < 0.05).CONCLUSIONS: Results show promise for combined play therapy and storytelling intervention to enhance the social skills of elementary school children diagnosed with ADHD.